A carcinoid tumor arising from a mature cystic teratoma in a 25-year-old patient: a case study. Issue 1 (December 2016) - Kim, Joo-Yeon
Abstract Background Mature cystic teratomas (MCTs) are common benign tumors occurring in the ovaries. Malignant transformation of teratomas (TMT) occurs in 1–3 % of all MCTs, usually in postmenopausal women. Squamous cell carcinoma is the most common tumor type. Primary carcinoid tumors of the ovary are uncommon, representing only 0.3 % of all carcinoid tumors and less than 0.1 % of all ovarian cancers. Case presentation A carcinoid tumor of the trabecular type arising from a MCT is presented in a 25-year-old woman. TMT was detected incidentally. Histologically, uniform, polygonal cells were arranged in a cord and trabecular pattern. Immunohistochemical staining showed positivity for neuro-specific enolase, synaptophysin, and CD56. Conclusions This case represents a very rare example of carcinoid tumor occurring in a woman younger than 30 years of age. Our findings suggest that sufficient tumor sampling is necessary to avoid overlooking small lesions, which, in our case, were not detected on either radiologic or gross examination.